2022
DOI: 10.1186/s12917-022-03219-2
|View full text |Cite
|
Sign up to set email alerts
|

The first evaluation of the effectiveness of canine vaccination schedule by two commercial vaccines in Iran

Abstract: Background Canine Parvovirus type 2 (CPV-2) is a member of the Parvoviridae family with a global distribution and causes pathogenicity in puppies aged from 6 weeks to 6 months. It should be noted that Maternally Derived Antibodies (MDA) have protection against CPV-2 in the first weeks of puppies’ life. However, MDA declines with age. The most important influential factor is timely vaccination against CPV-2. Methods In this study, 24 healthy 8-week-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
1
0
2
Order By: Relevance
“…One of them even died, which suggested that their vaccine-induced immunity was not sufficient to fully protect them against FPV at the time of infection. To understand the reason why the tiger cubs were not protected from FPV infection despite vaccination, we concentrated on the host-related vaccine failure induced by MDA, which is well documented in young animals and has been recognized as one of the most common reasons for vaccine failure in cats and dogs [ 45 , 46 , 47 , 48 ]. According to this hypothesis, kittens that receive high levels of MDA may fail to respond to a final dose of the FPV vaccine at 16 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
“…One of them even died, which suggested that their vaccine-induced immunity was not sufficient to fully protect them against FPV at the time of infection. To understand the reason why the tiger cubs were not protected from FPV infection despite vaccination, we concentrated on the host-related vaccine failure induced by MDA, which is well documented in young animals and has been recognized as one of the most common reasons for vaccine failure in cats and dogs [ 45 , 46 , 47 , 48 ]. According to this hypothesis, kittens that receive high levels of MDA may fail to respond to a final dose of the FPV vaccine at 16 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
“…Lebenswoche hinaus (bis zur 18. Lebenswoche) persistieren und mit der Impfung interferieren können 62 , 63 , 64 . Von einigen Autoren wird daher angeregt, Welpen-Impfungen, bis zur 20.…”
Section: Impfversagen Und Dessen Ursachenunclassified
“…Anjing harus menerima booster dalam waktu 1 tahun setelah vaksinasi utama diberikan atau kapan saja antara 26 dan 52 minggu. Vaksinasi diberikan dengan interval 3 tahun atau lebih(Decaroa et al, 2020).Gambar 1 menunjukkan hasil penelitian yang dilakukanShams et al, (2022), melihat titer antibodi 24 anak anjing terrier (12 ekor jantan dan 12 ekor betina) yang dibagi menjadi kelompok A, B, dan C. Kelompok A disuntikkan 1 ml normal saline, kelompok B disuntikkan vaksin Biocan DHPPi+L Bioveta, Czech, dan kelompok C disuntikkan vaksin Duramune Max 5+LCI/GP; Fort Dodge Animal Health, USA. Hasil penelitian ini membuktikan bahwa pada vaksinasi pertama, kelompok B telah menghasilkan antibodi sedangkan kelompok A menghasilkan antibodi pada vaksinasi kedua.…”
unclassified